ACADEMIC INTEGRITY POLICY PRACTICES AROUND THE WORLD: COMPARATIVE PERSPECTIVES AND LESSONS FOR HIGHER EDUCATION - Nasiba Rakhimova (Modern American Journals, 2025)
This article presents a comparative analysis of academic integrity policy practices across different regions of the world, including North America, Europe, Australia, Asia, Africa, and the Middle East. It examines how cultural, institutional, and governance factors influence the development and implementation of these policies. The study identifies both shared principles—such as defining misconduct, preventing plagiarism, and fostering ethical scholarship—and region-specific practices, such as honor codes in North America or national quality assurance integration in Europe. Special attention is given to contemporary challenges, including contract cheating, digital technology misuse, and the growing influence of artificial intelligence. The article concludes with recommendations for creating context-sensitive yet globally informed integrity frameworks that strengthen trust in higher education.
Keywords: Academic integrity, higher education policy, plagiarism prevention, honor codes, global education, ethics, contract cheating, educational governance